Recurring Issues from a Decade of Evaluation : Lessons for the IMF. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2014)
This report seeks to help the IMF enhance its effectiveness by identifying major recurring issues from the IEO's first 20 evaluations and assessing where they stand. The IMF's core areas of responsibility are surveillance, lending, and capacity development. The aim of this report is to strengthen the follow-up process by focusing on key issues that recurred in IEO evaluations, rather than on specific recommendations on their implementation. The IEO believes that a framework of reviewing and monitoring recurring issues would be useful in establishing incentives for progress, strengthening the Board's oversight, and providing learning opportunities for the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet